Effect of Zinc on Translocation of Iron in Soybean Plants - Ambler, J. E. (1970)
Zinc interfered with translocation of iron from roots to above ground parts of Glycine max. (L.) Merrill var. Hawkeye. During periods in which zinc impeded iron translocation, it also suppressed the production of reductant by roots. Addition of iron, as a ferric metal chelate (iron ethylenediaminedihydroxyphenylacetic acid), to the growth medium overcame the interference of zinc. In the root epidermis, potassium ferricyanide formed a precipitate (Prussian blue) with ferrous iron derived from the previously supplied iron ethylenediaminedihydroxyphenylacetic acid. The reduction of ferric iron was suppressed by zinc.